Smart metering road map for Nepal. (Asian Development Bank, 2018)
This publication summarizes the proposed activities and plans for the Nepal Electricity Authority on the implementation of a smart electricity grid. Prepared under the Power Transmission and Distribution Efficiency Enhancement Project in Nepal, the road map also explains the guiding principles, decision framework, and methodology used to manage the transition to new technologies.